Environmental exposure of a simulated pond ecosystem to a CuO nanoparticle-based wood stain throughout its life cycle. Issue 11 (26th October 2018) - Auffan, Mélanie; Liu, Wei; Brousset, Lenka; Scifo, Lorette; Pariat, Anne; Sanles, Marcos; Chaurand, Perrine; Angeletti, Bernard; Thiéry, Alain; Masion, Armand; Rose, Jérôme
Abstract : Indoor aquatic mesocosms were used to assess the behavior of a wood stain containing CuO nanoparticles in a simulated pond ecosystem for 1 month. Abstract : Indoor aquatic mesocosms were used to assess the behavior of fragmented products of a wood stain containing CuO nanoparticles in a simulated pond ecosystem for 1 month. By-products of degradation containing Cu are likely to be released during the use and end-of-life of this wood stain. Cu (bio)transformation and (bio)distribution within different environmental compartments ( e.g. water, sediments, and benthic grazers) were carefully analyzed. Because of the presence of the stain matrix, CuO nanoparticles contained in fragmented products were less bio-physical–chemically transformed (dissolution, complexation) with respect to pristine nanoparticles. After 28 days, only 1% of the Cu injected following fragmented product exposure remained in the water column (0.08 μg L −1 ), and 10% for the pristine CuO nanoparticles (2.67 μg L −1 ). Among these ∼10%, ∼51% were dissolved Cu species (1.35 μg L −1 ). These results are discussed with respect to the ecological compartments in which they accumulated, and to the doses to which aquatic organisms with distinct life traits were exposed.